2001
DOI: 10.1149/1.1360204
|View full text |Cite
|
Sign up to set email alerts
|

Pit Initiation on Stainless Steels in 1 M NaCl With and Without Mechanical Stress

Abstract: The onset of pitting corrosion at MnS inclusions on 304 stainless steel in 1 M NaCl was studied with and without applied mechanical stress with use of microelectrochemical cells. Polarization curves of areas ͑100 m diam͒ without inclusion showed no pitting at potentials below that of oxidation evolution; stress had no effect on the corrosion behavior. Areas containing five round inclusions of about 4 m in size showed stable pitting at about 400 mV; the effect of stress shifted the pitting potential to values t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 30 publications
5
115
0
2
Order By: Relevance
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the solution-treated specimen, many current spikes were generated above 0.4 V, and the current density rapidly increased and exceeded 0.1 A m −2 at 0.67 V. The potential region for MnS dissolution has been reported to be around 0.5 V in NaCl solutions. 13,14,[17][18][19]24 The many current spikes around 0.5 V were due to the dissolution of the sulfide inclusions, suggesting that the inclusions were likely the initiation sites for pitting. 17 In the case of the sensitized specimen, a sharp increase in the current density appeared suddenly at 0.32 V. The pitting potential of the sensitized specimens were determined to be around 0.3 V.…”
Section: Resultsmentioning
confidence: 99%
“…Microelectrochemical measurements are powerful techniques for the analysis of the electrochemical properties of a small area of a material. [13][14][15] However, the occurrence of crevice corrosion between a sensitized grain boundary and the masking of the electrode area was expected. A micro-TIG (tungsten inert gas) welding technique was applied to prevent crevice corrosion.…”
mentioning
confidence: 99%
“…Furthermore, these basic corrosion data can be used to simulate pit initiation and propagation. One very successful method for determining the corrosion characteristics of secondary phase particles is the electrochemical microcell method, which uses a small capillary filled with electrolyte, the tip of which permits electrochemical analysis of specific particles [11,[35][36][37][38][39][40]. This method has been employed with both synthesized intermetallic compounds (IMCs) and/or actual alloy substrates [11,17,34,[41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Anodic polarization measurements of the specimens with an exposed area of around 1 cm 2 indicated an increase in the pitting corrosion potential of the carburized stainless steels with interstitial carbon compared to untreated stainless steels. 1,[3][4][5] The microscopic anodic polarization measurements of the carburized stainless steel with a micro-scale electrode area (around 150 μm × 300 μm) containing an MnS inclusion, which is known to act as an initiation site of the pitting of stainless steels, [10][11][12][13][14][15][16][17][18][19][20][21] demonstrated that no pitting was initiated on the carburized stainless steel despite the presence of the MnS inclusion. 6 The micro-scale electrode areas were in situ observed by an optical microscope with a water immersion objective lens (a lateral resolution of ca.…”
mentioning
confidence: 99%